When your authority fluctuates throughout the day - ANICICH, Eric M. (Institutional Knowledge at Singapore Management University, 2021)
For many of us, the power we feel at work — how much, when it occurs, and around whom — can fluctuate. This can result in a surprising increase in stress and a decrease in well-being. To address this, consider these strategies for making power imbalances more manageable. First, be deliberate in scheduling your tasks to cluster activities with similar levels of power together. Second, give your work a routine and consider “theming” together days with similar activities. Third, create a role-transcendent identity in order to embrace your different levels of power. And finally, work to actively manage your well-being.